Dengue biting again : A five year retrospective study in a tertiary care hospital - Rupinder Bakshi; Sarjiwan Kaur; Satinder Kaur (GMC Patiala Journal of Research and Medical Education, 2019)
Dengue fever is caused by an arbovirus worldwide, especially in the tropical and sub-tropical regions. Its clinical manifestations range from mild fever to a severe disease characterized by hemorrhage and shock. This is transmitted to humans by day-biting Aedes aegypti and Aedes albopictus mosquitoes. Methods: A total of 18637cases were detected in last five years (2014-2018). 5 ml blood sample was collected from the suspected cases of Dengue, which were tested by NS1 Antigen detection by NS1Ag ELISA and for IgM antibody by IgM MAC ELISA depending upon the duration of fever. Results: Out 0f 18637, 10447 cases were positive for Dengue infection. The infection was more in males as compare to females and was more common in the age group of 21-40 years (42.2%). The disease is more prevalent in urban areas (69%) as compare to rural areas(31%). It was revealed from the present study that the trend of dengue infection is keep on increasing with each successive year from 2014 to 2018. Conclusion: Dengue affects humans of all age-groups and causes high moratlity. Thus, a rapid and accurate dengue diagnosis is of paramount importance for effective control of dengue outbreaks.